MEDIA LINGKUNGAN SEKITAR DALAM PENGEMBANGAN MINAT BELAJAR ANAK - Made Suardani (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2021)
The purpose of this study is to get a picture of the application of environmental media in the development of child study at kindergarten. The kind of research used in this study is qualitative. The object of research used in this study is the teachers of group B, children, and the principal of the elementary school. The data-collection technique used was observation, interview and documentation. The data analysis techniques used are the reduction of data, the presentation of data and drawing conclusions. Research indicates that practices use the environmental media of natural and artificial environments to develop a child's interest in learning with Expressed interest (a verbal expression expressed whether a child likes or dislikes an object), Manifest interest (interest expressed by actions or actions in which the child participates in an activity and the child participates in activities), tested interest (interest expressed from the child's knowledge or skill test conclusion in an activity), and interest inventoried (interest measured in answering questions given).